Avaliação das propriedades químicas em solo de cerrado SOB reflorestamento ciliar - da Silva, Alexandre Marques [UNESP]; Canuto, Daniela Sílvia de Oliveira [UNESP]; de Moraes, Mario Luiz Teixeira [UNESP]; Buzetti, Salatiér [UNESP] (My University, 2012)
The rapid growth of agriculture, promoted by public government initiatives, favored an out of control deforestation of our forests; today, reforestation of permanent preservation areas are necessary for the conservation of our natural resources, and recovery of such areas are required by public laws. In an area of 5.26 acres of riparian reforestation in the savanna soil chemical properties were evaluated after twenty years of planting. It was analyzed the following variables: (P, organic matter (MO), pH, K, Ca, Mg, H+Al, Al and S) in 13 modules, with three replicas in two depths (0 - 20 and 20 - 40 cm) in a randomized block design in hierarchical scheme. Reforestation with tree species on the edge of Parana river in Selvíria (MS) contributes to chemical soil attributes, under riparian reforestation, as similar as a soil without human disturbance in this region; it is also possible to verify that forestry plantation promotes deposition of organic material which is essential for nutrient cycling, which keep the chemical properties of such soil in good condition for the establishment of riparian vegetation.
Evaluation of chemical properties of savanna soil under riparian reforesting
Keywords: Riparian forest; Riparian reforestation; Savanna; Soil chemical properties